2020
DOI: 10.3389/fphys.2020.573660
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Shoe Mass on Performance and Running Economy in Trained Runners

Abstract: The aim of this study was to assess the effects of adding shoe mass on running economy (RE), gait characteristics, neuromuscular variables and performance in a group of trained runners. Methods: Eleven trained runners (6 men and 5 women) completed four evaluation sessions separated by at least 7 days. The first session consisted of a maximal incremental test where the second ventilatory threshold (VT 2) and the speed associated to the VO 2max (vVO 2max) were calculated. In the next sessions, RE at 75, 85, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
30
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(32 citation statements)
references
References 49 publications
2
30
0
Order By: Relevance
“…Running bouts were performed by all participants using the same footwear model (Joma R.3000) (weight: 258 g; EVA foam midsole; drop: 8 mm) avoiding diff erences in shoe mass and footwear properties and therefore [ 27 ] diff erences between participants, which could aff ect RE and biomechanical variables [ 28 ] . The treadmill gradient was set at 1 % to most accurately refl ect the energetic cost of outdoor running [ 29 ] .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Running bouts were performed by all participants using the same footwear model (Joma R.3000) (weight: 258 g; EVA foam midsole; drop: 8 mm) avoiding diff erences in shoe mass and footwear properties and therefore [ 27 ] diff erences between participants, which could aff ect RE and biomechanical variables [ 28 ] . The treadmill gradient was set at 1 % to most accurately refl ect the energetic cost of outdoor running [ 29 ] .…”
Section: Methodsmentioning
confidence: 99%
“…RE was measured as the energy cost of running (kJ • kg -1 • km -1 ), with the average respiratory exchange ratio (RER) during the same period and VO 2 caloric equivalent (kcal/l O 2 -1 ) used in previous research [ 27 ] . The equation used was the following Lusk [ 30 ] :…”
Section: Methodsmentioning
confidence: 99%
“…However, there is evidence that the role of footwear mass is relevant to an athlete's locomotive performance. For example, the effect on running economy of carrying extra weight on the foot has been shown to be significant with additional masses of both 50 g and 100 g [29] or ultimately during running then being measured at 1% per 100 g per foot [30]. Whilst several studies have investigated and successfully validated inertial or piezoelectric sensor technology for race walking [17,[36][37][38][39], these do not seemingly report the mass of the proposed technology to then be able to estimate their impact on the race walkers performance.…”
Section: Do Sbs Provide An Unfair Advantage?mentioning
confidence: 99%
“…In the case of additional technology to footwear such as SBS, this could also be in the form of their additional mass. Whilst the magnitude of shoe mass could be seen as arbitrary, this has been proposed to contribute towards negative performance [29,30] or acts as a deviation from the athletes nominal shoe mass which could then contribute towards athletic injury [31]. Whilst such studies often do not isolate the shoes mass from its cushioning or motion control aspects, it was reported that a shoe mass addition of 50 g could still affect performance [32].…”
Section: Is the Introduction Of Sbs Harmful To The Health Of The Athl...mentioning
confidence: 99%
“…SS and DS exercises and instructions are shown in Figure 2. Maximal oxygen uptake (VO 2max ), respiratory exchange ratio (RER), heart rate (HR), and blood lactate concentration ([La] + ) were chosen as dependent variables to describe physiological and metabolic responses [34]. Physiological parameters were continuously monitored during the running-until-exhaustion test.…”
Section: Dynamic Stretching Session (Ds)mentioning
confidence: 99%